If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5(x + -2) = 14 Reorder the terms: 3x + 5(-2 + x) = 14 3x + (-2 * 5 + x * 5) = 14 3x + (-10 + 5x) = 14 Reorder the terms: -10 + 3x + 5x = 14 Combine like terms: 3x + 5x = 8x -10 + 8x = 14 Solving -10 + 8x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 8x = 14 + 10 Combine like terms: -10 + 10 = 0 0 + 8x = 14 + 10 8x = 14 + 10 Combine like terms: 14 + 10 = 24 8x = 24 Divide each side by '8'. x = 3 Simplifying x = 3
| x+1=37+10 | | 5x^2-x+15=0 | | 3y-6=11 | | 8x+24=3x+4 | | 3x-1=29 | | 33334+3456789986= | | 12(5-x)=72 | | 3x-15=-15 | | 6t-18+8t=14t+35-8 | | 4x-6=5x+6 | | y=3-3y | | 7*-1+1= | | 7*-2+4= | | 7*-10+4= | | 5x+50=500 | | 3(x+1)=8 | | 7*0+4= | | 2(3*0+1)= | | 7x^2+66x+27=0 | | 3n-2=-26 | | 2(3x-10+1)= | | 5x^2-14=0 | | 2(3x-2+1)= | | 20x-50=25-5x | | 2(3x-1+1)= | | 9x^2-9x-4=0 | | 2x+7x-10=4x+3-2x | | u^2-3u-12=0 | | -8z-9=32 | | 2a^2x^2-abx-3b^2=0 | | x^2+2ax=3a^2 | | -20x^2+23x+7=0 |